Geochemistry of a late quaternary loess-paleosol sequence in central Argentina - Rouzaut, Sabrina (2019)
A loess-paleosol sequence in central Argentina was geochemically analyzed. Corralito I sequence (32°00‘7” S, 64°11’08” W, 469 m a.s.l) is composed by three paleosols and a buried soil separated by loess layers. Weathering indices (CIA, CIW, LWI), elemental ratios (ΣBases/Al2O3, Rb/Sr, CaO/TiO2, Na2O/TiO2), and mean annual paleo-precipitation indices (MAPPs) were calculated in order to obtain a weathering insight and to probe geochemical paleoclimatic proxies. The results indicate an incipient weathering degree throughout the sequence, without significant geochemical differences between paleosols and the loess mantles. Moreover, geochemical paleoclimatic proxies (MAPPs) do not detect a significant paleoprecipitation variability for the time period recorded in the studied loess-paleosol sequence.